Allocating Remedial Expenditures at the East Helena Smelter Complex, MT USA. Issue 1 (30th March 2021) - Davis, Andy; Evans, G.; Benateigha, S.; Clark, J.
Abstract: The East Helena, MT lead smelter complex was operated from 1888 through 2001 by Asarco. An adjacent zinc smelter was run by Anaconda (now ARCO) from 1926 through 1972. Both operations contaminated groundwater that migrated offsite under East Helena. As part of their bankruptcy settlement, Asarco paid $111.4 M toward remediation of site soil and groundwater. ARCO denied any liability so Asarco sued ARCO for response costs, relying in part on historical documents, photographs and soil and groundwater chemistry in the vicinity of Anaconda's zinc smelter. Based on expert analysis, the trial court determined that ARCO was liable for 25% of the $61.4 million actually spent. On appeal, the 25% allocation was upheld with the proviso that future costs may also be recovered after they are incurred.